Penguatan Kelembagaan Bumdes Desa Cokro Melalui Reorganisasi Dan Penataan Struktur Organisasi - Amidi, Amidi; Prasetiyo, Budi; Munahefi, Detalia Noriza; Ardiansyah, Adi Satrio (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Village-Owned Enterprises (BUMDes) play a strategic role in strengthening economic independence and optimizing local village potential. However, in various regions, including Cokro Village, Tulung District, Klaten Regency, several BUMDes have experienced institutional stagnation, resulting in the suboptimal functioning of their organizations. One such example is BUMDes Tirta Kencana, which had been inactive due to weak organizational structure and management. This community service activity aimed to reactivate the BUMDes through an institutional strengthening strategy based on reorganization and organizational structure arrangement. The implementation methods included problem identification, community socialization and forums, managerial training, reorganization deliberations, development of institutional documents, also mentoring and evaluation. The activity was carried out using a participatory-collaborative approach that actively involved the community in every stage. The results showed an increase in community awareness of the importance of village institutions, the formation of a new and more functional organizational structure, the preparation of standard operating procedures (SOPs) and annual work plans, as well as an improvement in the managerial capacity of the administrators, as reflected in the increase in average understanding scores from 56.3 to 80.1 (an increase of 42%). These findings confirm that a participatory-collaborative approach is effective in reactivating inactive BUMDes while building community commitment to program sustainability.